In the heat of the night: Temperature and vegetation structure disparity in habitat suitability for scaled quail - Katherine A. Travis; Caleb M. McKinney; Evan P. Tanner; Ashley M. Tanner; Fidel Hernández; Leonard A. Brennan; David G. Hewitt; Humberto L. Perotto-Baldivieso; Ryan S. Luna; R. Dwayne Elmore; John McLaughlin (Journal of Thermal Biology, 2026)

Use of NAMs in a weight of evidence approach to evaluate the safety via the inhalation route of acetylated vetiver oil, in spray products - Fanny Boisleve; Hind Assaf Vandecasteele; James Baily; Kamil Czuchrowski; Malik Diop; Catherine Gadras; David Herbst; Christina Hickey; Amaia Irizar; Boris P. Müller; Nikaeta Sadekar; Paul Sterchele; et al. (Regulatory Toxicology and Pharmacology, 2025)

Who’s at the table? Disaster committee composition and policy pathways after Hurricane Sandy - Timothy Fraser; Lucy Hewitt; Jessica Chen; Matthew Cherkerzian; Vincent Rago; Daniel P. Aldrich (Journal of Environmental Management, 2025)

Heat-set gelation of milk- and fermentation-derived β-lactoglobulin variants - Zheng Pan; Remco Kornet; Sheelagh Hewitt; Alan Welman; Jeremy P. Hill; Marcel Wubbolts; Stephen Mitchell; Warren C. McNabb; Aiqian Ye; Alejandra Acevedo-Fani; Skelte G. Anema (Food Hydrocolloids, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

S10-01 Making safety decisions for a sunscreen active ingredient using next-generation risk assessment: benzophenone-4 case study - M.T. Baltazar; S. Cable; A. Punt; N.J. Hewitt; B. Nicol; P. Kukic; S. Scottt; S. Malcomber; R. Mascarenhas; C. Alexander-White; J. Reynolds; J. Houghton; et al. (Toxicology Letters, 2024)

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

P16-33: Identifying and characterizing toxicity liabilities of pharmaceuticals using ToxProfiler: A blinded case study with the ITLF consortium - B. Ter Braak; L. Wolters; K. Elbertse; M. Beilmann; H. Boonen; A. Doherty; F. Van Goethem; P. Hewitt; J. Hornberg; J. Koch; S. Kusterman; J. Lyon; et al. (Toxicology Letters, 2023)

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Brown bullhead at the St. Lawrence River (Cornwall) Area of Concern: health and endocrine status in the context of tissue concentrations of PCBs and mercury - M. D. O. Pinheiro; D. B. D. Simmons; M. Villella; G. R. Tetreault; D. C. G. Muir; M. E. McMaster; L. M. Hewitt; J. L. Parrott; B. J. Park; S. B. Brown; J. P. Sherry (Environmental Monitoring and Assessment, 2020)

Poor nutrition as a potential cause of divergent tree growth near the Arctic treeline in northern Alaska - Sarah B. Z. Ellison; Patrick F. Sullivan; Sean M. P. Cahoon; Rebecca E. Hewitt (Ecology, 2019)
Trees growing near the Arctic treeline have long been used to reconstruct past climates. However, recent studies have shown deterioration of historically strong positive correlations between air temperature and tree growth (known as “divergence”). Divergence has important implications for confidence in paleoclimate reconstructions and ecosystem–atmosphere carbon exchange. Studies in the Brooks Range of northern Alaska showed that white spruce in the west increased growth in response to late 20th century warming, whereas those in the east failed to show a growth increase. In an earlier study across four watersheds in the Brooks Range, we tested and rejected the hypothesis that divergence in the easternmost watershed reflects moisture limitation of growth. Here, using 16 sites distributed across the same four watersheds, we tested an alternative hypothesis, that greater nutrient limitation in the east may have impeded positive growth responses to warming. Climate comparison across the four Brooks Range study watersheds revealed that, although the easternmost watershed generally had a drier growing‐season climate, the most consistent difference was that winter air temperature and both winter and summer soil temperatures were much colder in the central and eastern watersheds. Soil nutrient availability, foliar nutrient concentrations, and tree growth were all generally lower in the central and eastern than in the western watersheds. Foliar phosphorus concentration was the best predictor of spatial variation in branch extension growth—a finding that is somewhat inconsistent with the theory that forest productivity on young, glacially derived soils should be strongly nitrogen limited. Experimental fertilization yielded the greatest growth increase in the eastern, an intermediate response in the central, and the smallest growth increase in the western watershed, generally mirroring trends in soil temperature, soil nutrient availability, foliar nutrient concentrations, and growth of control trees. Our results confirm that growth in the easternmost watershed is more nutrient limited and suggest that phosphorus limitation may be at least as important as nitrogen limitation of growth. We hypothesize that cold soil effects on tree access to nutrients might explain divergence in the eastern Brooks Range and elsewhere near the Arctic treeline, particularly in areas with cold winters and widespread permafrost.

Automation in cell and gene therapy manufacturing: from past to future - P. Moutsatsou; J. Ochs; R. H. Schmitt; C. J. Hewitt; M. P. Hanga (Biotechnology Letters, 2019)
As more and more cell and gene therapies are being developed and with the increasing number of regulatory approvals being obtained, there is an emerging and pressing need for industrial translation. Process efficiency, associated cost drivers and regulatory requirements are issues that need to be addressed before industrialisation of cell and gene therapies can be established. Automation has the potential to address these issues and pave the way towards commercialisation and mass production as it has been the case for ‘classical’ production industries. This review provides an insight into how automation can help address the manufacturing issues arising from the development of large-scale manufacturing processes for modern cell and gene therapy. The existing automated technologies with applicability in cell and gene therapy manufacturing are summarized and evaluated here.

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Arctic summer sea-ice seasonal simulation with a coupled model: Evaluation of mean features and biases - P P Saheed; Ashis K Mitra; Imranali M Momin; E N Rajagopal; Helene T Hewitt; Ann B Keen; Sean F Milton (Journal of Earth System Science, 2019)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Growing Canopy on a College Campus: Understanding Urban Forest Change through Archival Records and Aerial Photography - Lara A. Roman; Jason P. Fristensky; Theodore S. Eisenman; Eric J. Greenfield; Robert E. Lundgren; Chloe E. Cerwinka; David A. Hewitt; Caitlin C. Welsh (Environmental Management, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Evidence-based selection of training compounds for use in the mechanism-based integrated prediction of drug-induced liver injury in man - Sanja Dragovic; Nico P. E. Vermeulen; Helga H. Gerets; Philip G. Hewitt; Magnus Ingelman‐Sundberg; B. Kevin Park; Satu Juhila; Jan Snoeys; Richard J. Weaver (Archives of Toxicology, 2016)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Identifying uncertainties in Arctic climate change projections - Daniel L. R. Hodson; Sarah P. E. Keeley; Alex West; Jeff Ridley; Ed Hawkins; Helene T. Hewitt (Climate Dynamics, 2013)

Plant pest and disease diagnosis using electronic nose and support vector machine approach - Reza Ghaffari; Jullada Laothawornkitkul; Daciana Iliescu; Evor Hines; Mark Leeson; Richard Napier; Jason P Moore; Nigel D Paul; C Nicholas Hewitt; Jane E Taylor (Journal of Plant Diseases and Protection, 2012)

Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Erratum to: Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Debris-flow impact, vulnerability, and response - P. M. Santi; K. Hewitt; D. F. VanDine; E. Barillas Cruz (Natural Hazards, 2011)

In Vivo and In Vitro Mixed-Function Oxygenase Activity and Vitellogenin Induction in Fish and in Fish and Rat Liver Cells by Stilbenes Isolated from Scotch Pine (Pinus sylvestris) - Joanne L. Parrott; Jagmohan Kohli; James P. Sherry; L. Mark Hewitt (Archives of Environmental Contamination and Toxicology, 2011)

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes - David P. Dimasi; Jern Y. Chen; Alex W. Hewitt; Sonja Klebe; Richard Davey; John Stirling; Elizabeth Thompson; Robin Forbes; Tiong Y. Tan; Ravi Savarirayan; David A. Mackey; Paul R. Healey; et al. (Human Genetics, 2010)

Investigation of first year biotic and abiotic influences on the recruitment of pike Esox lucius over 48 years in Windermere, U.K. - C. G. M. Paxton; I. J. Winfield; J. M. Fletcher; D. G. George; D. P. Hewitt (Journal of Fish Biology, 2009)
Estimated pike Esox lucius recruitment varied by a factor of 16 for females from 1944 to 1991 and by a factor of 27 for males from 1943 to 1990 in Windermere, a temperate, mesotrophic U.K. lake. No significant stock–recruitment relationships were found, but analysis with general additive models (GAMs) revealed that early autumnal water temperature, strength and direction of the North Atlantic Oscillation displacement (corresponding to different climatic conditions in winter) and zooplankton abundance but above all, late summer water temperature were important explanatory variables over the entire time series. Female recruitment was also influenced by young‐of‐the‐year winter temperature. There was no evidence that perch Perca fluviatilis year‐class strength, lake level or the summer position of the Gulf Stream influenced recruitment. The fitted models explained up to c. 65% of the overall observed variation between years.

A comparison of PMIP2 model simulations and the MARGO proxy reconstruction for tropical sea surface temperatures at last glacial maximum - Bette L. Otto-Bliesner; Ralph Schneider; E. C. Brady; M. Kucera; A. Abe-Ouchi; E. Bard; P. Braconnot; M. Crucifix; C. D. Hewitt; M. Kageyama; O. Marti; A. Paul; et al. (Climate Dynamics, 2009)

Evaluation of coupled ocean–atmosphere simulations of the mid-Holocene using palaeovegetation data from the northern hemisphere extratropics - J. Wohlfahrt; S. P. Harrison; P. Braconnot; C. D. Hewitt; A. Kitoh; U. Mikolajewicz; B. L. Otto-Bliesner; S. L. Weber (Climate Dynamics, 2008)

Apparent autosomal dominant keratoconus in a large Australian pedigree accounted for by digenic inheritance of two novel loci - Kathryn P. Burdon; Douglas J. Coster; Jac C. Charlesworth; Richard A. Mills; Kate J. Laurie; Cecilia Giunta; Alex W. Hewitt; Paul Latimer; Jamie E. Craig (Human Genetics, 2008)

Development of an Ecologic Marine Classification in the New Zealand Region - Ton H. Snelder; John R. Leathwick; Katie L. Dey; Ashley A. Rowden; Mark A. Weatherhead; Graham D. Fenwick; Malcolm P. Francis; Richard M. Gorman; Janet M. Grieve; Mark G. Hadfield; Judi E. Hewitt; Ken M. Richardson; et al. (Environmental Management, 2007)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

The impact of year-to-year changes in the weather on the dynamics of Daphnia in a thermally stratified lake - D. G. George; D. P. Hewitt (Aquatic Ecology, 2006)

European colonization by the spined loach ( Cobitis taenia ) from Ponto‐Caspian refugia based on mitochondrial DNA variation - MARK A. CULLING; KAREL JANKO; ALICJA BORON; VICTOR P. VASIL’EV; ISABELLE M. CÔTÉ; GODFREY M. HEWITT (Molecular Ecology, 2006)
In the last 20 years, new species, asexual reproduction, polyploidy and hybridization have all been reported within the genus Cobitis . An understanding of the current distribution and baseline phylogeographical history of ‘true’ nonhybrid Cobitis species is crucial in order to unravel these discoveries. In the present work, we investigated the phylogeography of the spined loach, Cobitis taenia , using 1126 bp of the mitochondrial cytochrome b gene from 174 individuals collected at 47 sites. In total, 51 haplotypes that differed at 49 positions (4.35%) were detected. We deduce that C. taenia survived European glaciations in at least three refuges in the Ponto‐Caspian area. Two of these refuges each provided a major lineage that recolonized Europe in separate directions: one westward to England and the other spreading north into Russia before moving west. A third (minor) lineage that contributed little to the recolonization of Europe was also revealed — remaining near its Black Sea refuge. However, more recent history was difficult to resolve with colonization from a more western refugium during the last glacial maximum (LGM) a distinct possibility. Nested clade analysis indicates a pattern of restricted gene flow with isolation by distance at the first two levels and overall. Unlike many other European freshwater fish species, the Danube is not part of the current distribution of C. taenia, nor was it used as either a refuge or a source of colonization of Europe. Low genetic diversity within C. taenia suggests that its colonization of Europe is relatively recent. Demographic analyses revealed a history of recent expansion and isolation by distance.

A multi-model analysis of the role of the ocean on the African and Indian monsoon during the mid-Holocene - Y. Zhao; P. Braconnot; O. Marti; S.P. Harrison; C. Hewitt; A. Kitoh; Z. Liu; U. Mikolajewicz; B. Otto-Bliesner; S.L. Weber (Climate Dynamics, 2005)

Behavioural and pharmacological magnetic resonance imaging assessment of the effects of methylphenidate in a potential new rat model of attention deficit hyperactivity disorder - Katherine N. Hewitt; Yasmene B. Shah; Malcolm J. W. Prior; Peter G. Morris; Chris P. Hollis; Kevin C. F. Fone; Charles A. Marsden (Psychopharmacology, 2005)

Biotic and abiotic influences on the recruitment of male perch in Windermere, U.K. - C. G. M. Paxton; I. J. Winfield; J. M. Fletcher; D. G. George; D. P. Hewitt (Journal of Fish Biology, 2004)
Perch Perca fluviatilis recruitment (based on the catch per unit effort, CPUE, of 2 or 3 year male perch) varied greatly from 1941 to 1995 in Windermere, U.K., with year class strengths strongly synchronous between the two basins of this temperate, mesotrophic lake. Statistically significant modified Ricker (Saila‐Lorda) stock‐recruitment curves could be fitted to data from three of four sampling sites, while the presence of widespread disease and late summer water temperature were also important explanatory variables. Multiple‐regression analyses revealed no influences of pike Esox lucius recruitment, zooplankton abundance, or the climatic influences ( i.e . North Atlantic Oscillation and displacement of the summer position of the Gulf Stream) on perch recruitment over and above associated influences from temperature. Fitted models realistically explained up to c . 60% of the observed variation in perch recruitment.

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

The Relationship Between Spatial Distribution and Diet of Arctic Charr, Salvelinus Alpinus, In Loch Ness, U.K. - Ian J. Winfield; Colin W. Bean; Diane P. Hewitt (Environmental Biology of Fishes, 2002)

Mitochondrial DNA, ecology and morphology: interpreting the phylogeography of the Nesotes (Coleoptera: Tenebrionidae) of Gran Canaria (Canary Islands) - D. J. Rees; B. C. Emerson; P. Oromí; G. M. Hewitt (Molecular Ecology, 2001)
The genus Nesotes (Coleoptera: Tenebrionidae) is represented in the Canary Islands by 19 endemic species, the majority of which are single island endemics. Nesotes conformis and N. fusculus are described on four and three islands, respectively, but each forms a paraphyletic assemblage between Gran Canaria and the other islands. The other described species for Gran Canaria are N. quadratus , N. lindbergi and N. piliger . Thirty‐six individuals representing the five species on Gran Canaria have been sequenced for 675 bp of the mitochondrial DNA (mtDNA) cytochrome oxidase II gene. Neighbour‐joining analysis of maximum likelihood distances resulted in five distinct mtDNA lineages for N. quadratus , two of which also include mitotypes of N. conformis . Each of the other three species is found on only one mtDNA lineage. We propose from the molecular data that differentiation in a widespread N. quadratus ‐type ancestor was followed by morphological adaptation to coastal, pine and laurel forest habitats.

Concordance of interannual fluctuations in acoustically estimated densities of Antarctic krill around South Georgia and Elephant Island: biological evidence of same-year teleconnections across the Scotia Sea - A. S. Brierley; D. A. Demer; J. L. Watkins; R. P. Hewitt (Marine Biology, 1999)

Isolation and characterization of microsatellite loci in European hake, Merlucius merlucius (Merlucidae, Teleostei) - P. Morán; C. Lundy; C. Rico; G. M. Hewitt (Molecular Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Responses of the phytoplankton to a deliberate attempt to raise the trophic status of an acidic, oligotrophic mountain lake - C. S. Reynolds; G. H. M. Jaworski; J. V. Roscoe; D. P. Hewitt; D. G. George (Hydrobiologia, 1998)

Localization of the cell death genes CPP32 and Mch-2 to human Chromosome 4q - J. Nasir; J. L. Theilmann; V. Chopra; A. M. Jones; D. Walker; D. M. Rasper; J. P. Vaillancourt; J. E. Hewitt; D. W. Nicholson; M. R. Hayden (Mammalian Genome, 1997)